Implementasi Model Problem Based Learning untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi IPAS Kelas IIID SDN 057 Palembang - Linawati, Dina; Sari, Diah Kartika; Sulaiman, Reki; Lestari, Diah Ayu; Maryani, Dwi; Trijulianti, Ega; Triani, Endang (SJEE (Scientific Journals of Economic Education), 2024)
This research was conducted with the aim of improving student learning outcomes in science learning using the Problem Based Learning learning model. This research method uses a classroom action research design consisting of two cycles, where one cycle consists of 1 meeting. The stages of each cycle consist of four stages, namely planning, implementation, observation and reflection. The subjects in this research were class III D students at SDN 57 Palembang, totaling 24 students, consisting of 11 male students and 13 female students. Data collection techniques use observation techniques and tests on student learning outcomes. This research shows that the average daily test scores achieved by students in the pre-cycle stage reached 68. There were 10 students (42%) who completed their studies (reached the KKM). 14 students (58%) did not complete their studies (under the KKM). Meanwhile, after carrying out cycle one, there were 17 (71%) students who achieved learning completeness (KKM), while 7 (29%) students did not achieve learning completeness. Therefore, it can be concluded that the research results show that the use of the Problem Based Learning learning model can improve the learning outcomes of class V students at SDN 57 Palembang